Epistemic Akrasia and Belief‐Credence Dualism. (18th June 2021) - Jackson, Elizabeth; Tan, Peter
Abstract: We call attention to certain cases of epistemic akrasia, arguing that they support belief‐credence dualism. Belief‐credence dualism is the view that belief and credence are irreducible, equally fundamental attitudes. Consider the case of an agent who believes p, has low credence in p, and thus believes that they shouldn't believe p. We argue that dualists, as opposed to belief‐firsters (who say credence reduces to belief) and credence‐firsters (who say belief reduces to credence) can best explain features of akratic cases, including the observation that akratic beliefs seem to be held despite possessing a defeater for those beliefs, and that, in akratic cases, one can simultaneously believe and have low confidence in the very same proposition .